2017
DOI: 10.1097/adm.0000000000000272
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of E-cigarette Use, Health Status, and Risk and Protective Health Behaviors in Adolescents

Abstract: Objectives E-cigarettes (ECs) are increasingly popular among adolescents, who perceive them as “safer” than cigarettes. Although research has examined risk factors for adolescent EC use, little is known about how EC use correlates with health status and protective health behaviors. Methods 2,488 adolescents (mean age=17.31, SD=0.67; 46% male) completed a survey on EC and cigarette use, physical and mental health, physical activity, diet, sleep, and alcohol and other drug (AOD) use. Logistic regression compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 44 publications
2
49
1
2
Order By: Relevance
“…Other recent studies show that hookah (water pipe) use is similarly associated with greater marijuana use among U.S. high school seniors and college students (Goodwin et al, 2014;Palamar, Zhou, Sherman, & Weitzman, 2014). Emerging research on e-cigarettes has documented an association between e-cigarette use and use of alcohol, marijuana, and other illicit substances (Demissie, Everett Jones, Clayton, & King, 2017;Westling, Rusby, Crowley, & Light, 2017), although much of this research compares ecigarette use to cigarette use or dual use of both cigarettes and e-cigarettes (Dunbar et al, 2017;Kristjansson, Mann, & Smith, 2017;McCabe, West, Veliz, & Boyd, 2017).…”
Section: Introductionmentioning
confidence: 97%
“…Other recent studies show that hookah (water pipe) use is similarly associated with greater marijuana use among U.S. high school seniors and college students (Goodwin et al, 2014;Palamar, Zhou, Sherman, & Weitzman, 2014). Emerging research on e-cigarettes has documented an association between e-cigarette use and use of alcohol, marijuana, and other illicit substances (Demissie, Everett Jones, Clayton, & King, 2017;Westling, Rusby, Crowley, & Light, 2017), although much of this research compares ecigarette use to cigarette use or dual use of both cigarettes and e-cigarettes (Dunbar et al, 2017;Kristjansson, Mann, & Smith, 2017;McCabe, West, Veliz, & Boyd, 2017).…”
Section: Introductionmentioning
confidence: 97%
“…Researchers recently concluded that dual use of electronic cigarettes with conventional tobacco is associated with decreased sleep quality in women [21]. Other researchers who examined sleep data on 2488 California adolescents found no significant difference in weekday sleep time duration between adolescents who used electronic cigarettes at a higher frequency and lower frequency, although adolescents who used electronic cigarettes slept significantly less on weekends compared with adolescents who did not use electronic cigarettes [22].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that smoking is associated with an unhealthy lifestyle [35,36]. Similarly, an association between health risk behaviour and e-cigarettes use has been reported [37]. However, to our knowledge, the relationship between new products and healthy behaviour among adolescents has not been sufficiently investigated.…”
Section: Discussionmentioning
confidence: 89%